(untitled) (Research, Society and Development, 2023)
Nowadays, the teaching of chemistry in Brazil has not met the requirements for training citizens as questioners of reality. Most of the time, traditional teaching methodologies are adopted, which are limited to mere expository teaching in the classroom. This manuscript contrasts with the traditional view of teaching by using new teaching methodologies, such as texts, didactic videos, conceptual maps, didactic games, and interactive-exposition classes already used in the traditional method. The manuscript aims to strengthen the critical view and citizens’ posture based on CTS (Science, Technology, and Society) teaching and the National Curricular Base (BNCC), focusing on the biodiesel theme, in addition to improving the performance of learning organic chemistry content. For this, a qualitative, discursive and critical study was employed. The study was conducted with the generating theme of biodiesel, which is widely discussed in the media. This subject was used to study esters and atmospheric pollution in a third-grade classroom at Luciano Cabral Duarte State High School, located in Aracaju - SE. The application of a didactic film, along with conceptual maps and didactic games, led to an improvement in the understanding of chemical and environmental concepts related to biodiesel productions.